PENERAPAN METODE PEMBELAJARAN KOOPERATIF STRUKTUR TWO STAY TWO STRAY (TSTS) DISERTAI PETA KONSEP TERHADAP HASIL BELAJAR BIOLOGI SISWA KELAS VIII SMP N 32 SOLOK SELATAN - Rilla, Wiska Oktavia (Pendidikan Biologi, 2014)
The background of this research is about the studentsâ low learning score in IPA lesson especially biology. Sceleton system material is difficult that is caused many students get score below KKM at SMPN 32 Solok Selatan. This case happens because the teaching learning process is only main for the teacher and does not interact with the students. Otherwise, to see the condition of school does not prepare media alike framework of human model. The purpose of the research is to know the effect applying of Cooperative Learning Structure Two Stay Two Stray (TSTS) with Concept Map toward the Studentsâ Learning Score at Class VIII SMP N 32 Solok Selatan. The technique of sampling uses total sampling. The analysis data analyzes by using t exam. Based on the research, this case can be concluded that applying of Cooperative Learning Structure Two Stay Two Stray (TSTS) with Concept Map toward the Studentsâ Learning Score at Class VIII SMP N 32 Solok Selatan. The score of attitude can be concluded the studentsâ behavior in experiment class is better control class meanwhile the studentsâ ability in control class than experiment class.